The Relationship Between Serum Concentration of Vitamin D, Total Intracranial Volume, and Severity of Depressive Symptoms in Patients With Major Depressive Disorder - Zhu, Dao-min; Zhao, Wenming; Zhang, Biao; Zhang, Yu; Yang, Ying; Zhang, Cun; Wang, Yajun; Zhu, Jiajia; Yu, Yongqiang (Frontiers in Psychiatry, 2019)
Background: Depression has been linked to vitamin D deficiency. However, little attention was paid to the neural substrate underlying this association. Methods: 50 patients with major depressive disorder (MDD) were enrolled in this study. High-resolution structural magnetic resonance imaging was performed to calculate total intracranial volume (TIV). Peripheral venous blood samples were collected to measure serum vitamin D concentration. Hamilton Rating Scale for Depression (HAMD) was used to assess severity of depression symptoms. The relationship among TIV, serum vitamin D concentration and HAMD score was examined using correlation, linear regression and mediation analyses. Results: In patients with MDD, HAMD score was negatively correlated with TIV and serum vitamin D concentration, and TIV was positively correlated with serum vitamin D concentration. Linear regression analyses showed TIV and serum vitamin D concentration were significant predictors of HAMD score. Importantly, mediation analysis revealed that TIV significantly mediated the relationship between serum vitamin D concentration and HAMD score. Conclusion: Our findings suggest that TIV may serve as a potential neural biomarker for monitoring responses to adjuvant therapy of vitamin D in patients with MDD.